Acute Drought Is an Important Driver of Bark Beetle Infestation in Austrian Norway Spruce Stands - Netherer, Sigrid; Panassiti, Bernd; Pennerstorfer, Josef; Matthews, Bradley (Frontiers in Forests and Global Change, 2019)
Infestations by the Eurasian spruce bark beetle, Ips typographus have recently caused peaks in Norway spruce mortality in Central European forests. In this study, we examined how temperature conditions, chronic and acute drought stress, and stand characteristics influence forest disturbance by the spruce bark beetle. We investigated bark beetle induced salvage logging in Norway spruce stands of Austrian Federal Forests (ÖBf) as a proxy variable for infestation/attack by I. typographus. Utilizing ÖBf forest inventory data and the monitoring tool PHENIPS-TDEF, a well-proven bark beetle phenology model combined with a forest water balance module, we retrospectively simulated effective temperature sums for bark beetle development and transpiration deficits at forest stand level. We examined forest stand properties and the model output variables as predictors of bark beetle attack in decision trees and binary logistic regression analysis. We found that I. typographus infestation increased with a stand predisposition index indicating high share of Norway spruce, increased stand age, and stand density. Stands subject to bark beetle attack in the previous year were highly prone to subsequent damage, which points to attack pressure from increased population densities due to ample supply of breeding material. While chronically dry soil conditions described as shallow, xeric, and of low moisture, were associated with bark beetle infestation to a lesser degree, acute drought in the form of increases in stand transpiration deficits proved to raise the probability of bark beetle attacks. The previous year's and current year's summer (June to August) TDEF total, in combination with effective thermal sums allowing for at least two bark beetle generations and sister broods, were significant predictors of bark beetle attack. We conclude from our results that in the absence of windthrow, a combination of ample host availability, favorable temperature conditions for bark beetle development, and acute disposition of trees to attack caused by drought stress can intensify population growth and very likely lead to bark beetle mass outbreaks.